Separation and Characterization of Free-PSA and Its Complexes in Benign and Malignant Uterus Tumors - Al-salihi, Jwan (Iraqi Journal of Science, 2025)
Gel filtration chromatography was used to separate free -anti total PSA antibody frora the complexes of anti total PSA antibody with the PSA immunoreactive isoforms [Free-PSA (F-PSA) and the complex of PSA with o antichymotrypsin (PSA-ACT)] in benign and malignant uterus tumors tissues in order to estimate the ratio of (F-PSA-PSA) or F-PSA%. The data obtained revealed that these ratios are different in benign patients from those of malignant patients. Spectrophotometric studies using UV. range (200-350 nm) was performed on PSA, anti total PSA antibody, and their complexes in both cases. The results revealed the presence of more than one type of complexes from the same tissue homogenate in both cases. Polyacrylamid electrophoresis was also performed to characterize the differences and the similarity between the PSA complexes in tissue homogenates of benign and malignanit uterus tumors.